Basic structure constitutionalism : revisiting Kesavananda Bharati - Sanjay S. Jain; Sathya Narayan (Eastern Book Co., 2011)
Collection of contributed papers presented at the event, Revisiting Kesavananda Bharati, organized by Centre for Public Law, ILS Law College, Pune, India on Jan. 16, 2010; includes invited papers; festschrift for Indian lawyers, Nani Palkhivala and H.M. Seervai.